A randomised controlled trial of an iPad‐based application to complement early behavioural intervention in Autism Spectrum Disorder. (25th May 2017) - Whitehouse, Andrew J.O.; Granich, Joanna; Alvares, Gail; Busacca, Margherita; Cooper, Matthew N.; Dass, Alena; Duong, Thi; Harper, Rajes; Marshall, Wendy; Richdale, Amanda; Rodwell, Tania; Trembath, David; et al.
Abstract : Background: Technology‐based interventions for Autism Spectrum Disorder (ASD) have proliferated, but few have been evaluated within the context of a randomised controlled trial (RCT). This RCT evaluated the efficacy of one technology‐based early intervention programme (Therapy Outcomes By You; TOBY) in young children with ASD. Methods: TOBY is an app‐based learning curriculum designed for children and parents as a complement to early behavioural intervention. Eighty children (16 female) were recruited to this RCT within 12 months of receiving a diagnosis of ASD ( M age = 3.38; SD  = 0.69) and randomised to receive either treatment‐as‐usual (community‐based intervention, n  = 39) or the TOBY therapy (at least 20 min/day) plus treatment‐as‐usual ( n  = 41) for a period of 6 months. Outcomes were assessed at 3 and 6 months postbaseline. (Australian New Zealand Clinical Trials Registry: ACTRN12614000738628; www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=365463 ). Results: Children in the TOBY intervention group averaged 19 min/day engaging with the app in the first 3 months, but only 2 min/day during the second 3 months. There was no group difference in scores on the primary outcome, the Autism Treatment Evaluation Checklist, at either the 3‐ or 6‐month follow‐up. However, significant improvements at the 6‐month follow‐up were observed in the TOBY intervention group relative to the treatment‐as‐usual group on three secondary outcomes: the Fine Motor and Visual Reception subscales of the Mullen Scale of Early Learning and the Total Words Understood scale of the MacArthur‐Bates Communicative Development Index. Statistical trends towards improvement in the TOBY intervention group were observed on measures of adaptive function, although these decreased in magnitude from the 3‐ to 6‐month follow‐up. Conclusions: This study provides evidence that technology‐based interventions may provide a relatively low‐cost addition to existing therapist‐delivered interventions for children with ASD. However, sustained use of the app over the full 6‐month period was a challenge for most families.